(5w-3)-(w-1)=

Simple and best practice solution for (5w-3)-(w-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5w-3)-(w-1)= equation:


Simplifying
(5w + -3) + -1(w + -1) = 0

Reorder the terms:
(-3 + 5w) + -1(w + -1) = 0

Remove parenthesis around (-3 + 5w)
-3 + 5w + -1(w + -1) = 0

Reorder the terms:
-3 + 5w + -1(-1 + w) = 0
-3 + 5w + (-1 * -1 + w * -1) = 0
-3 + 5w + (1 + -1w) = 0

Reorder the terms:
-3 + 1 + 5w + -1w = 0

Combine like terms: -3 + 1 = -2
-2 + 5w + -1w = 0

Combine like terms: 5w + -1w = 4w
-2 + 4w = 0

Solving
-2 + 4w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 4w = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 4w = 0 + 2
4w = 0 + 2

Combine like terms: 0 + 2 = 2
4w = 2

Divide each side by '4'.
w = 0.5

Simplifying
w = 0.5

See similar equations:

| y=x^3+3x^2-72x+5 | | -3v-6+8=-15 | | -4+x=-7x+4 | | -4+x=-7+4 | | 5/7x4/35 | | 7y=37-2 | | -2(6d-7)=-30+4d | | ((80*x)-4)=(7*(x+9)) | | 1/2(x-8)=-2-5/2x | | 1+4x=3x-9 | | -(-5-3x)=6x-10 | | -21+5b=2(7b+4) | | 10k+2(-5-7k)=5k+6 | | X(5-3x)=7x+4 | | 2+x=4-9(x-4) | | 2y+3y-6(y+2)=y+6 | | 5(7-2a)=30 | | 5x+4+1=59+1 | | -4(-4k-5)=8k-12 | | 6x-5-7x=10-4x+3 | | 2/3x=17/4 | | 5+6(1+2f)=23 | | -27x^2+342x+72=0 | | 5n-2n=27 | | 23+18=-21+14y | | 12=0.005*x | | 7-y=-7+y | | -3(1/3)= | | 4b-30=b-3 | | -3(3)+5= | | 1225+280+80= | | X-(1/4)X-(1/3)X-10=0 |

Equations solver categories